Hot−yet−suppressed under PD−1 blockade: an RMP–NRF2–PD−L1 axis associated with a reduced proportional response in hepatocellular carcinoma - Zuo, Mingzhu; Li, Haiqiang; Chen, Na; Guo, Zengjun; Wan, Zhenghua (Frontiers in Immunology, 2026)
Immune checkpoint blockade (ICB) provides therapeutic benefits to a subset of patients with hepatocellular carcinoma (HCC); however, reliable predictors of treatment efficacy remain scarce. This study investigates whether RPB5-mediating protein (RMP) facilitates the alignment of redox adaptation with immune checkpoint regulation, thereby influencing the extent of therapeutic benefit under programmed cell death protein 1 (PD-1) blockade. In Hepa1–6 and Hep3B cell lines, enforced expression of RMP resulted in elevated levels of NRF2 and PD-L1 proteins, alongside enhanced clonogenic growth and short-term migratory capacity. In a subcutaneous Hepa1–6 tumor model, RMP-overexpressing tumors exhibited accelerated growth and a distinct immunohistochemical profile characterized by increased levels of RMP, NRF2, PD-L1, Ki-67 and HO-1, indicative of a proliferative and redox-adapted state. Upon administration of anti-PD-1 therapy, both experimental cohorts demonstrated tumor regression; however, the RMP-overexpressing cohort exhibited a proportionally reduced inhibition compared to controls, despite experiencing greater absolute tumor shrinkage from a higher baseline. This suggests a limited response amplitude within the RMP/NRF2-high context. Post-therapy tissues from the overexpression cohort exhibited elevated levels of RMP, NRF2, HO-1, and PD-L1, alongside an immune microenvironment characterized by an increased presence of CD3/CD8 cells and a decreased presence of CD4/CD25 cells. This pattern is indicative of an inflamed yet suppressed state of adaptive immune resistance. Collectively, these observations support a model wherein continuous RMP–NRF2–HO-1 activity and persistent PD-L1 expression exert inhibitory pressure, even as PD-1 blockade facilitates cytotoxic T-cell infiltration. This dynamic accounts for the relatively lower inhibition observed in the overexpression context. The combined RMP/NRF2/PD-L1 signature proposes a mechanistically informed biomarker framework and suggests the potential for rational therapeutic combinations that pair PD-1 blockade with modulation of the redox pathway in HCC.